Principales medios de control de mosca blanca (Bemisia tabaci Gennadius, 1889) en el cultivo de rábano (Raphanus sativus). - MURRIETA DIAZ, JOSE DANIEL (2023)
The most important whitefly in the radish crop is Bemisia tabaci (Gennadius, 1889), which causes damage by sucking the sap from the plants, weakening them and causing their death, as well as transmitting viral diseases. The information was collected through the technique of analysis, synthesis and summary in order to inform the reader about the main means of control of whitefly (B. tabaci Gennadius, 1889) in the cultivation of radish (R. sativus). From the above, it was determined that the direct damage is caused by nymphs and adults causing the appearance of chlorotic spots on the radish plant, affecting its growth and subsequently causing its death. The greatest damage is due to the ability to transmit viral diseases (nymphs are also capable of acquiring the virus) and B. tabaci is considered the most common and economically important virus vector internationally. Cultural practices for the control of B. tabaci are as follows: live barriers, high planting densities, plastic mulches and trap crops, which contribute to the reduction of pest insect populations. The use of yellow sticky traps allows the reduction of pest populations and the application of insecticides; however, it must be taken into account that in these traps it is also possible to locate biological controllers, particularly parasitoid wasps. The parasitoid most commonly applied through periodic releases is the species Encarsia formosa; this parasitoid only produces females, which is an advantage, since each one released has the capacity to parasitize whitefly nymphs and pupae. The application of Abacmectin at a dose of 3 cm3 per liter of water is recommended for the control of B. tabaci within the radish crop, being more effective and economically more feasible.